Alkylresorcinol, a biomarker for whole grain intake, and its association with osteoarthritis: the MOST study. Issue 10 (October 2022) - Zertuche, J.-P.; Rabasa, G.; Lichtenstein, A.H.; Matthan, N.R.; Nevitt, M.; Torner, J.; Lewis, C.E.; Dai, Z.; Misra, D.; Felson, D.
Summary: Introduction: Higher intake of fiber has been associated with lower risk of incident symptomatic osteoarthritis (OA). We examined whether levels of alkylresorcinol (AR), a marker of whole grain intake, were associated with OA in subjects in The Multicenter Osteoarthritis (MOST) Study. Method: Knee x-rays and knee pain were assessed at baseline and through 60-months. Stored baseline fasting plasma samples were analyzed for AR homologues (C17:0, C19:0, C21:0, C23:0, C25:0) and total AR levels (AR sum). Two nested case–control studies, one for incident radiographic OA and one for incident symptomatic OA were performed with participants re-assessed at 15, 30 and 60 months. Multivariable conditional logistic regression with baseline covariates including age, sex, BMI, physical activity, quadriceps strength, race, smoking, depressive symptoms, diabetes and knee injury tested the association of log transformed AR levels with OA outcomes. Results: Seven hundred seventy-seven subjects were, on average, in their 60's, and most were women. For 60-month cumulative incidence, there was no significant association between quartiles of AR concentration and incident radiographic (e.g., for incident radiographic OA, highest vs lowest quartile of AR sum showed RR = 0.93 (95% CI 0.59, 1.47), and for symptomatic OA RR was 1.22 (95% CI 0.76, 1.94). In secondary analyses examining 30-month incidence, high AR levels were associated with a reduced risk of X-ray OA (RR = 0.31 (95% CI 0.15, 0.64). Conclusion: In primary analyses, AR levels were not associated with risk of OA, but secondary analyses left open the possibility that high AR levels may protect against OA.